Ultrasound and CBCT analysis of blood flow and dimensions of the lingual vascular canal: A case control study - Tabrez Lakha; Mohit Kheur; Sven Mühlemann; Supriya Kheur; Bach Le (Journal of Oral Biology and Craniofacial Research, 2021)
Objective: To assess the correlation between the diameter of the mandibular lingual vascular canal (MLVC) as determined on CBCT examination to blood flow and arterial diameter as determined by ultrasound Doppler analysis (USG) in dentate and edentulous patients. Methods: 20 subjects were equally distributed into two groups based on the status of their dentition. Group 1 included dentate subjects (DE) and Group 2 included edentulous subjects (ED).The subjects from both the groups underwent CBCT scan for the assesement of the diameter of the MLVC.Similarly, USG was done to assess the diameter of the sublingual artery anastomosis and blood flow in the anterior mandible. Data was analysed using Karl Pearson’s Correlation coefficient test and Student’s unpaired ‘t’ test. Results: Irrespective of the status of the dentition and age, a positive correlation was noted between the diameter of foramen on CBCT examination and the diameter of anastomosing artery as studied by the USG (r ​= ​0.290).Similarly, a positive correlation was observed between the diameter of foramen on CBCT and the volume of blood entering the mandible (r ​= ​0.447).A positive correlation (r ​= ​0.138) was observed between the diameter of the anastomosing artery and the volume of blood entering the mandible. Conclusion: The anterior mandible has a rich vascular supply independent of age and status of the dentition.The dimensions and location of MVLC could be assessed on a CBCT prior to implant placement so that the operating surgeon has an idea about the vascularity of the region. Further studies with higher sample size should be undertaken to confirm these findings.